Policy knowledge among ‘elite citizens’ - Jensen, Carsten; Zohlnhöfer, Reimut (European policy analysis, 2020)
We have a very limited understanding of citizens’ knowledge about their social rights. It is well-established that people on average know little about politics and research also suggests that many harbor substantial misperceptions about the outcomes of benefit systems in terms of the amount of fraud, trends in claims, and overall costs. Yet, we lack solid insights into people's knowledge about the design of social rights (what we label ‘policy knowledge’ for short). It is precisely this knowledge on the design of social policies, however, which is of prime importance for scholars of social policy because this is what governments actually change when reforming the welfare state. Employing survey evidence from Denmark and Germany, we try to address this lacuna. We find a mixed picture in the sense that policy knowledge in a few specific issues is high, but typically, when the issue has been salient in the public. Overall, policy knowledge is low.
Gesehen am 02.03.2021